2007
DOI: 10.1160/th06-06-0313
|View full text |Cite
|
Sign up to set email alerts
|

Platelet microparticle membranes have 50- to 100-fold higher specific procoagulant activity than activated platelets

Abstract: Platelet microparticles (PMPs) are small vesicles released from blood platelets upon activation. The procoagulant activity of PMPs has been previously mainly characterized by their ability to bind coagulation factors VIII and Va in reconstructed systems. It can be supposed that PMPs can contribute to the development of thrombotic complications in the pathologic states associated with the increase of their blood concentration. In this study, we compared procoagulant properties of calcium ionophore A23187-activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
132
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 451 publications
(145 citation statements)
references
References 34 publications
5
132
0
2
Order By: Relevance
“…Platelet-derived MPs have been shown to be more prothrombotic than platelets themselves [39], and lower circulating PMPs are seen in patients that suffer from hemorrhagic complications after trauma [40]. In parallel with these studies, we noted a relative increase in PMPs 24 h after TBI and an associated increase in clot firmness at this time.…”
Section: Discussionsupporting
confidence: 73%
“…Platelet-derived MPs have been shown to be more prothrombotic than platelets themselves [39], and lower circulating PMPs are seen in patients that suffer from hemorrhagic complications after trauma [40]. In parallel with these studies, we noted a relative increase in PMPs 24 h after TBI and an associated increase in clot firmness at this time.…”
Section: Discussionsupporting
confidence: 73%
“…They are considered essential for hemostasis, as they expose phospholipids, adhesion receptors, and TF on their surface, providing binding sites for activated clotting factors and thrombin generation [12, 25, 26]. It has been reported that PMPs have 100-fold higher procoagulant activity than platelets [27]. We and others have documented that PMP are the most abundant MP in the healthy population [11, 12].…”
Section: Discussionmentioning
confidence: 99%
“…Despite there being some reports to the contrary (Tushuizen et al 2012), numerous studies have shown that platelet EVs are procoagulant due to the exposure of negatively charged PS which can enhance clot formation (for review see Hargett & Bauer (2013)). Indeed, platelet EVs have more binding sites for the factors involved in the clotting cascade than do activated platelets themselves (Sinauridze et al 2007). More recent studies have revealed the presence of TF on the surface of endothelial-and monocyte-derived EVs (Breitenstein et al 2010), as well as P-selectin glycoprotein ligand-1 which can bind to P-selectin on the surface of activated platelets and become incorporated into the clot (Falati et al 2003).…”
Section: The Role Of Evs In Coagulopathiesmentioning
confidence: 99%